(untitled) (TSUL LEGAL REPORT, 2026)
This article explores the legal foundations for the emergence of limited rights to use land plots and examines the historical development of servitudes within the Central Asian khanates. Servitudes were primarily formed through agreements between communities and were regulated by evolving and traditional governance systems. During the khanate period, the forms of servitudes, including rights of access to land and the use of natural resources, evolved to reflect the cultural and social needs of society. In the Soviet era, the monopolization of land and natural resources as state property halted the development of servitudes. However, by the late 20th century, following the collapse of Soviet rule, legislation and regulations related to servitudes were revised, paving the way for their integration into the modern legal framework. In the Republic of Uzbekistan, the contemporary regulation of servitudes is being implemented through new provisions in the Land Code. This process serves as a crucial legal foundation for land and property management, introducing new forms of legal relationships and enhancing their economic and social significance. Servitudes play an important role in the country’s economic development, particularly in the fields of agriculture and infrastructure. Proper and effective regulation of servitudes helps improve relations between landowners and other legal entities. Furthermore, efficient mechanisms are being developed to define the legal basis of servitudes and resolve related disputes.